A Study Of The Community In Ilir Barat And Ilir Timur Districts, Palembang City - Kurniati; Addinul Ikhsan; Masagus Fathir Fadhillah (CV. Doki Course and Training, 2026)
This study aims to analyze the influence of Sharia financial literacy on the public's interest in becoming customers of Sharia banks. Data were collected via questionnaires distributed to 110 respondents across two districts in Palembang City—Ilir Barat and Ilir Timur—focusing specifically on the 100 respondents who had never conducted transactions with a Sharia bank. Data analysis was performed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method via the SmartPLS 4 application. The results indicate that Sharia financial literacy has a positive influence on the interest in becoming a Sharia bank customer, accounting for 52.8% of the effect. Furthermore, a T-statistic of 17.717 demonstrates that the hypothesis result is statistically significant, confirming a strong relationship between Sharia financial literacy and the public's interest in becoming Sharia bank customers. Based on these findings, the study recommends enhancing educational programs through various methods. Future research is encouraged to examine other independent variables.